Pendidikan Toleransi dan Relevansinya dengan Dinamika Sosial Masyarakat Indonesia - Sodik, Fajri (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
The State of Indonesia is known for its pluralistic ethnic society that is constantly undergoing changes in every aspect of life. Tolerance education embedded in society aims to make citizens aware of equality in the life of the nation and state so they are be able to form harmonious Indonesian society side by side. This paper aims to describe the importance of tolerance education in the social dynamics of Indonesian people living in diversity. The method used in this research is literature study (literature review). The results of this study indicate that tolerance education is very relevant in the social dynamics of Indonesian society. The tolerance values ​​that must be instilled by the Indonesian people in daily life include: mutual respect, brothers and sisters, freedom, cooperation, mutual help, non-discrimination and a culture of sharing. With the existence of tolerance education, the Indonesian people can live in harmony and spared from conflict and animosity between fellow citizens.